2012
DOI: 10.1021/nl2035964
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowire Esaki Diodes

Abstract: We report on the fabrication and characterization of silicon nanowire tunnel diodes. The silicon nanowires were grown on p-type Si substrates using Au-catalyzed vapor-liquid-solid growth and in situ n-type doping. Electrical measurements reveal Esaki diode characteristics with peak current densities of 3.6 kA/cm(2), peak-to-valley current ratios of up to 4.3, and reverse current densities of up to 300 kA/cm(2) at 0.5 V reverse bias. Strain-dependent current-voltage (I-V) measurements exhibit a decrease of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…This is traced back to an increased window for inelastic transmission across the device that scales with the bias window. Again, this trend fits with the experiments performed by Schmid et al [47] Carrier mobilities. Carrier mobilities limited by EPC is an important performance indicator of materials.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This is traced back to an increased window for inelastic transmission across the device that scales with the bias window. Again, this trend fits with the experiments performed by Schmid et al [47] Carrier mobilities. Carrier mobilities limited by EPC is an important performance indicator of materials.…”
supporting
confidence: 91%
“…In Fig. 2 we consider transport in a short (6.5 nm) and a long (19.6 nm) silicon p-n junction [7,47,48] with transport in the [100] crystal direction.…”
mentioning
confidence: 99%
“…The tunneling in forward-bias mode can be seen as negative differential conductance (NDC), i.e, a negative slope in current-voltage (I-V) curve. So far, tunneling in nanometer-scale p-n junctions has been reported in vertical nanowires in forward-bias mode [6,7] and in lateral gated p-n junctions in reverse-bias mode [8]. In this work, we study nanoscale lateral p-n junctions in forward-bias mode and report the experimental observation of NDC at low temperatures.…”
Section: Introductionmentioning
confidence: 91%
“…So far, research about tunneling in nanometer-scale pn junctions has been reported mainly for vertical structures [6][7][8]. Tunneling in lateral pn junctions has been reported by Aydin et al [9], but not in nanowire structures.…”
Section: Introductionmentioning
confidence: 98%